2014
DOI: 10.3389/fmicb.2014.00669
|View full text |Cite
|
Sign up to set email alerts
|

LDS1-produced oxylipins are negative regulators of growth, conidiation and fumonisin synthesis in the fungal maize pathogen Fusarium verticillioides

Abstract: Oxylipins are fatty acid-derived signaling compounds produced by all eukaryotes so far investigated; in mycotoxigenic fungi, they modulate toxin production and interactions with the host plants. Among the many enzymes responsible for oxylipin generation, Linoleate Diol Synthase 1 (LDS1) produces mainly 8-hydroperoxyoctadecenoic acid and subsequently different di-hydroxyoctadecenoic acids. In this study, we inactivated a copy of the putative LDS1 ortholog (acc. N. FVEG_09294.3) of Fusarium verticillioides, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…Functional and physiological analyses of LOXs were firstly addressed to dicots and recent researches aimed to unravel the role of LOX in plant-pathogen cross-talk with the use of maize mutants (Christensen et al, 2013;Gao et al, 2007) and Fv mutants (Lanubile et al, 2013;Scala et al, 2014). Our study provides the first insight of the overexpression of genes involved in the LOX pathway in resistant (R) and susceptible (S) maize lines, tested in field condition over a time course of 21 days after inoculation with Fv.…”
Section: Introductionmentioning
confidence: 96%
“…Functional and physiological analyses of LOXs were firstly addressed to dicots and recent researches aimed to unravel the role of LOX in plant-pathogen cross-talk with the use of maize mutants (Christensen et al, 2013;Gao et al, 2007) and Fv mutants (Lanubile et al, 2013;Scala et al, 2014). Our study provides the first insight of the overexpression of genes involved in the LOX pathway in resistant (R) and susceptible (S) maize lines, tested in field condition over a time course of 21 days after inoculation with Fv.…”
Section: Introductionmentioning
confidence: 96%
“…Although the functional and physiological characterization of LOXs was first addressed in dicots, only recently have studies aimed to unravel the role of oxylipins in monocot–pathogen interactions with the use of maize mutants (Christensen et al ., ; Gao et al ., ) and F. verticillioides mutants (Scala et al ., ). The analysis of the maize knock‐out lox3 mutant provided convincing genetic evidence that the functional host LOX3 isoform and its 9‐oxylipin products are required for normal biosynthesis of fumonisin B1 and conidiation by F. verticillioides (Gao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The role of F. verticillioides ‐derived oxylipins in endogenous processes was established by the inactivation of the LDS1 gene ( LDS1 ), where the deletion mutant (hereafter referred to as ΔFv lds1 D) was perturbed in development, secondary metabolism and virulence (Scala et al ., ). It was uncovered that LDS1‐derived oxylipins act as negative regulators of fumonisin synthesis.…”
Section: Introductionmentioning
confidence: 97%
“…The most susceptible genotypes exhibited higher contents of linoleic acid and higher production of VOCs compared to those of moderately resistant genotypes. Recent studies have shown that the composition of total fatty acids can influence infections of F. verticillioides and fumonisin accumulation in maize under field conditions (Scala et al ., ). Similar results were reported by Dall'Asta et al .…”
Section: Discussionmentioning
confidence: 97%